Analysis of the necessity and efficiency of the HEI diploma holder professional retraining needs in Adjara Autonomous Republic - George Abuselidze; Lia Davitadze (E3S Web of Conferences, 2020)
At the present stage, in the context of global economic and political problems, the educational space in countries with a small open economy is of particular importance, since it is recognized as one of the key elements of ensuring public welfare. In addition to the costs directly allocated to education in Georgia, the government finances various retraining courses, the need for which is due to the higher education programs which seem to be incompatible with the labour market. The purpose of this article is to determine the cost efficiency of retraining incurred by the state, and the reasons for these additional costs as well as the aspects of retraining (profession / qualification) provided to higher education diploma holders. This last group is of particular interest to us to determine what causes the need for services provided by the employment agency in the case of people with higher education which, possibly, leads us to gaps in study programs, which, in turn, can be caused by a) higher education programs, which cannot give graduates the proper skills; or/and b) the institution of higher education has not studied the required number of graduates/skills needed in the market (and determines the number of students according to its academic staff) and/or graduates with low academic performance (which are supported by the institution of higher education so as not to lose a voucher) need retraining.
Keywords: A20; A23; H52; I22; I23; I25; P36; R23; 330; Graduate; Analysis of Education; Educational Finance; Financial Aid; Higher Education; Education and Economic Development; Education and Training; Regional Labor Markets